Strategi Pemasaran Surat Kabar Lokal Kaltim Post di Samarinda - Ahmad Arib Billah; Tetra Hidayati; Rahmawati - (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
Developments in technology and information in the present requires the company to further enhance business performance to gain the trust of consumers hearts. The purpose of this study is: To find out how the marketing strategy at Kaltim Post Samarinda. In this study, researchers used a Cartesian diagram analysis tool that consists of four dimensions, namely, product, price, promotion, place. The study of 96 respondents using questionnaire method  Likers Scale. The collected data were analyzed using analytical methods of customer satisfaction, the results of this study indicate that the level of customer satisfaction with the marketing strategies of Kaltim Post Samarinda is between 20-40 which means low satisfaction, namely 31,01. From the comparison of the average performance score and the average score of hope 31,0146,27 indicates that consumers are still not satisfied with the services given.Keywords: Marketing Strategy, Cartesian diagram, Customer Satisfaction